Decreased serum levels of 25-OH vitamin D and vitamin K in patients with type 2 diabetes mellitus - Yang, Ling (Frontiers in Endocrinology, 2024)
Background: Insulin resistance and/or insulin secretion dysfunction are crucial causes of type 2 diabetes mellitus (T2DM). Although some studies have suggested potential roles for vitamins D and K in glucose metabolism and insulin sensitivity, there is limited and inconclusive research on their levels in T2DM patients and their relationship with blood glucose levels and insulin resistance. Additionally, there is a lack of large-scale clinical trials and comprehensive studies investigating the combined effects of vitamins D and K on T2DM. Methods: A total of 195 participants with newly diagnosed T2DM were included in the research group, while 180 volunteers undergoing physical examinations in our hospital served as the control group. Fasting plasma glucose (FPG) was estimated using the glucose-oxidase technique, and fasting serum insulin (FINS) was evaluated by radioimmunoassay. FPG and FINS were used to calculate the homeostasis model assessment-insulin resistance (HOMA-IR). Serum vitamin D levels were measured using 25-hydroxyvitamin D, and vitamin K levels were evaluated using phylloquinone (VK1) and menaquinone (VK2) via ultra-high performance liquid chromatography and tandem mass spectrometry. Receiver operating characteristic (ROC) analysis was performed to assess the predictive value of these vitamins for T2DM. Results: Circulating levels of 25-hydroxyvitamin D (25.95±10.42 ng/mL), VK1 (1.24±0.89 ng/mL), and VK2 (0.2 ±0.21 ng/mL) in T2DM patients were significantly lower than in the control group (37.46±13.95 ng/mL for 25-hydroxyvitamin D, 1.99±1.39 ng/mL for VK1, and 0.33±0.22 ng/mL for VK2; p<0.001 for all comparisons). ROC analysis indicated that 25-hydroxyvitamin D, VK1, and VK2 could predict the occurrence of T2DM, with AUC values of 0.75, 0.69, and 0.71, respectively. In T2DM patients, 25-hydroxyvitamin D levels were positively correlated with VK1 (r=0.43, p<0.001) and VK2 (r=0.40, p<0.001) levels. FPG and HOMA-IR in T2DM patients were negatively correlated with circulating levels of 25-hydroxyvitamin D (r=-0.57, p<0.001), VK1 (r=-0.44, p<0.001), and VK2 (r=-0.36, p<0.001). Conclusion: Circulating levels of vitamins D and K are lower in T2DM patients and show significant correlations with blood glucose levels and insulin resistance. These findings suggest that measurements of 25-hydroxyvitamin D, VK1, and VK2 could have predictive value for T2DM, highlighting the potential roles of these vitamins in T2DM management.